A Review and Comparison of Smoothing Methods for Solar Photovoltaic Power Fluctuation Using Battery Energy Storage Systems - Pinheiro, Aline L.; Ramos, Felipe O.; Neto, Martins M. B.; Lima, Rafael N.; Bezerra, Libina G. S.; Washington, A. (IEEE PES Conference On Innovative Smart Grid Technologies Latin America (Online), 2021)
Renewable sources are becoming an important share of power generation. Although very beneficial for the environment, their instability caused by weather conditions can lead to power quality issues when connected to the grid. In order to minimize those power fluctuations, a Battery Energy Storage System can be coupled, providing or absorbing energy. This paper aims to review a few smoothing algorithms, such as Simple Moving Average, Double Moving Average, Exponential Moving Average, Moving Median, Ramp Rate, and Modified Ramp Rate, and compare them to the same simulation conditions, a 307.8 k W p solar photovoltaic system, for the purpose of finding the most suitable way to maintain the variation within an acceptable range while preserving the battery health. As the result of the analysis, a modification made on the ramp rate algorithm proposed in this paper that enables the battery State of Charge to return to its ideal level, stands out positively regarding the other methods.